Absorption of I¹³¹ using oil palm activated carbon for radioactive spillage decontamination and waste management - Samsuddin, Noryasmin Yusrina (2020)
Introduction: Nuclear Medicine is one of the facilities that provide the diagnostic and treatment services to patients where usually used the radioactive material such as Tc99m and I131 to treat the disease. For treatment of thyroid disease, it done with the administration of radioactive I131 to patient. When the administrated radioactive material occurred, the risk of spillage is high. Hence, the proper and safe contamination management of radioactive materials is important component of radiation protection in hospital. Thus, this study is purposed a new technique for radioactive contamination management by using palm kernel activated carbon. Method: Sample of the pure I131 from the laboratory will be mixed with the palm kernel activated carbon with varies of concentration. The mixture that form will be filter using filter paper. After waited for 15 minutes, the sediment on the filter paper and the water residue will be form efficiency. The radioactivity of the sediment and water residue for varies concentration will be measured using dose calibrator. The measurement will be repeated at fourth, eighth, twelfth and sixteenth day. After that, the mixture of maximum concentration palm kernel will be taken and scan using SEM & EDX to see the morphology image and the element that found in sample. Result: The radioactivity of water residue and sediment decreases along the time exponentially shows the agglomeration and solidification process is occurred. Theoretically, the higher the concentration of the mixture occur, more agglomeration are occurred. However, some of the concentration of mixture are higher activity and lower for other at initial interactions. It is due to the agglomeration and solidification that occur in the both concentrations are lower than others concentration. Besides, the images from SEM shows the agglomerated and pore structure while the EDX analysis show the element that found in the sample. Conclusion: Palm kernel activated carbon is useful for all adsorption and neutralize the number of radiation where able to adsorb and evaporate the I131 from the laboratory. The radioactivity of sediment and water residue on sixteen day coincided to hypothesis and provided result. The image from the SEM and EDX analysis that show the morphology structure and the element that found in sample is one of the positively upcoming for the radioactivity contamination management.